Analisis Penggunaan Aplikasi Kaji Cepat Badan Penanggulangan Bencana Daerah (BPBD) Provinsi Sulawesi Tengah Terhadap Pelaporan Kebencanaan - Putra, Muhlis Dwi; Elvisa, Putri; Wirabuana, Satria (CV. Publikasi Indonesia, 2022)
This study analyzes the use of a rapid assessment application from the Regional Disaster Management Agency (BPBD) of Central Sulawesi Province. As is known, Central Sulawesi Province is one of the areas that has a fairly high vulnerability to natural disasters. This is because this island is the meeting point of three tectonic plates, namely the Pacific Plate which moves westward, the Eurasian Plate which moves south-south, and the smaller Philippine Plate. Therefore, based on the mandate of Law Number 24 of 2007, the BPBD was formed in order to strive for the implementation and service of the community in the field of regional disaster management. This study uses a qualitative descriptive research method with data collection techniques through in-depth interviews and observation. The results show that the disaster reporting system software through this rapid assessment application has produced a high-fidelity Prototype, but this application is still not perfect and will still be developed. This research goes through a process of analysis and software design based on valid data and information from literature studies as well as field studies and interviews by BNPB officers of Central Sulawesi Province who are related to parties related to disasters.